Konsep dan Urgensi Konstitusi dalam Kehidupan Berbangsa dan Bernegara - Al Munawaroh; Selva Octaria; Zaskya Rahmadani; Bambang Trisno (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This study explores the concept and urgency of the constitution in the context of national and state life. The Constitution is a fundamental legal document that provides a framework for the organization and operation of the state, as well as establishing the basic rights of citizens and limits on government power. The constitution also plays an important role in maintaining political stability, ensuring justice, and protecting human rights. The urgency of the constitution is reflected in its function as a basis for the supremacy of law, promoting national unity, and balancing power between state institutions. This study identifies that a good understanding of the constitution is important for the success of a democratic system and the sustainable development of a country.